2010
DOI: 10.1074/jbc.m110.154054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two APOBEC3F Splice Variants Displaying HIV-1 Antiviral Activity and Contrasting Sensitivity to Vif*

Abstract: Approximately half of all human genes undergo alternative mRNA splicing. This process often yields homologous gene products exhibiting diverse functions. Alternative splicing of APOBEC3G (A3G) and APOBEC3F (A3F), the major host resistance factors targeted by the HIV-1 protein Vif, has not been explored. We investigated the effects of alternative splicing on A3G/A3F gene expression and antiviral activity. Three alternatively spliced A3G mRNAs and two alternatively spliced A3F mRNAs were detected in peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…1). An additional recent report on the existence of a Vif-susceptible splice variant of huA3F composed largely of the CTD is also consistent with these data (36).…”
Section: Discussionsupporting
confidence: 79%
“…1). An additional recent report on the existence of a Vif-susceptible splice variant of huA3F composed largely of the CTD is also consistent with these data (36).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, it is certainly possible that A3F has multiple determinants that contribute to its interaction with Vif. In agreement with this, Lassen et al recently reported that the N terminus of A3F has domains that are involved in regulating Vif sensitivity (23).…”
Section: Discussionsupporting
confidence: 58%
“…Inactivation of the host restriction factors encoded by the apoplipoprotein B mRNA editing, enzyme catalytic polypeptide family of proteins by Vif (57), and the host counter-evasion of this strategy by producing APOBEC3F splice variants that are Vif resistant but that maintain antiviral activity (58) are prime examples. Because the nature of the HIV life cycle is such that multiple transcriptional splice variants are required for productive HIV replication, the ability of HIV to impact splicing of host transcripts is not surprising (59).…”
Section: Discussionmentioning
confidence: 99%